Financial literacy, experience, risk tolerance and investment behavior: Observations during pandemic - Mahat, Nur Alya Afiqah; Lau, Wei-Theng (Research and Scientific Innovation Society, 2023)
This paper investigates the relationships among financial literacy, investment experience, risk tolerance, and investment decision-making. The study, carried out in the top two populated states in Peninsular Malaysia, is to better understand investment behavior, especially during the coronavirus disease (COVID-19) pandemic. The target respondents are widely distributed across ages, academic qualifications, years of investment experience, occupations, and gender. The correlations and regressions propose significant relationships among financial literacy, investment experience, risk tolerance, and investment behavior. Generally, financial literacy, investment experience, and risk tolerance are important factors contributing to the investment decision-making prescribed, with experience typically outpacing literacy in our sample. At the same time, investment experience is found to be relevant in describing the level of risk tolerance. The result supports the importance of understanding finance to aid investment decision-making and manage investment risks. It contributes to the literature by covering experience as one of the factors in describing investment behavior. This year-2021 survey also helps to better understand investment behavior among Malaysians in recent days and during the pandemic.